The Effect of Abnormal Audit Fees on Internal Control Weakness - Raha Rajaei Khoramabad; Samane Edalati Shakib (Iranian Journal of Accounting, Auditing & Finance, 2020)
The present study aims to assess abnormal the effect of audit fees on listed firms' internal control weakness on Tehran Stock Exchange. The multivariate regression model is used for testing research hypotheses. Ordinary Least Squares and fixed effects regression are used for more confidence in the hypothesis's test results. The present study's data include 1309 listed observations on the Tehran Stock Exchange, which are analyzed during 2012-2018. Stata Software is employed for data analysis and testing the hypotheses. The results show that there is a positive and significant relationship between abnormal audit fees and internal control weakness, and such a conclusion can be indicative of the fact that audit quality is lower in firms with abnormal audit fees, so internal control weaknesses of such firms is more than that of the others. The study outcomes may give great strength to researchers and policymakers. In this paper, four variables of the financial weakness of internal control, nonfinancial weakness of internal control, weakness in the IT system, and delay in the audit report are used for the first time to evaluate internal control weakness better using the exploratory factor analysis.